PENGARUH PEMBERIAN NPK GROWER DAN KOMPOS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABE RAWIT (Capsicum frutescent L) - Maruli Maruli; Ernita Ernita; Hercules Gultom (DINAMIKA PERTANIAN, 2012)
This research aims to recognize the effect of interaction of NPK and Compost Doses on growth and production of chili. The research was carried out at experimental farm of Faculty of Agriculture Riau Islamic University during six months from February to July 2012. Completely Radomized Design with two factors and three replication was used.The first factor was M (NPK Gower Doses) with four levels, namely M0 (without Grower), M1 (15 g/plot), M2 (30 g/plot), and M3 (45 g/plot). The second factor was T (compost doses) with four levels, namely T0 (without compost), T1 (250 g/plot), T2 (500 g/plot), and T3 (750 g/plot). The observated parameters included plant height, flowering age, harvested age, fruit weight per plant, and number of residual fruit. The observation results show that NPK Grower and compost had a significant effect on flowering age, harvested age, and fruit weight per plant with the best interreaction of M1T3. The NPK application affected significantly on plant height, flowering age, harvested age, fruit weight per plant, and number of residual fruit with the best effect of M3. The compost application had a significant effect on plant height, flowering age, harvested age, fruit weight and number of residual fruit with the best effect of T3.